STUDENTS' CONTRIBUTION TO ENVIRONMENTAL CONSERVATION WITH A CENTERED CLEANING SYSTEM IN DARUL ULUM KUDUS ISLAMIC BOARDING SCHOOL - Aan Heri Ustadzi; Nur Rizqi Cholid (International Conference on Social and Islamic Studies, 2021)
This article describes the hygiene system (Ro'an) cleaning system and garbage utilization: The case study of Pesantren Salaf Darul Ulum Kudus, Ro'an is a term of hygiene activities in boarding schools. This method attempts to examine the status of a group of people, an object, a condition, a system of thought or current classes of events. From the results of the research of Hygiene systems (Ro'an) in the Pondok pesantren Darul Ulum This includes, the division of daily schedules and Ro'an, water technician channels, disposal of waste, disposal of waste channels shower, WC and public kitchen boarding schools. This holy Islamic Pesantren holds about 250 students and daughters. Therefore, students hygiene should be observed to prevent the onset of disease in the students. Including the purpose of this hygiene activity system (Ro'an) students to educate and embed a healthy lifestyle through the cleanliness system of boarding schools.